The Combination of Surgical Excision with Debulking Technique and Intralesional Triamcinolone Acetonide Injection in the Management of Keloid - Riana Miranda Sinaga; Desy Sahara Putri S (Talenta Publisher, 2025)
Abstract. Background: Keloid is a fibroproliferative disorder of the dermis resulting from abnormal wound healing, characterized by excessive collagen deposition, thickened and highly vascularized dermis, and abundant infiltration of inflammatory cells.The highest incidence of keloid occurs in individuals during their second decade of life. Case Ilustartion: A 16-year-old female presented to the Dermatology and Venereology Clinic at Prof. Chairuddin P. Lubis Hospital, Medan, with the chief complaint of a lump on the front and back of her left earlobe accompanied by itching for the past three years. Initially, 4 years ago, the patient complained of itching after ear piercing. Over time, a lump appeared at the site of the piercing. The lump was reported to have gradually increased in size over the past 2 years. Dermatological examination, there was a solitary erythema nodule with firm boundaries, with a spongy solid consistency, oval round shape and size 1.4x1.3x0.9 cm, regular edges, smooth surface in the region of the anterior auricularis lobule sinistra and posterior auricularis lobule sinistra. The patient was diagnosed with keloid. The patient was then planned for surgical excision with debulking technique and intralesional triamcinolone acetonide injection. Discussion: It is stated in the literature that combination treatment is the optimal strategy and from most studies it has been found that surgical excision combined with steroid injection shows a recurrence rate of less than 50%. Conclusion: Keloid treatment should be done in combination to reduce recurrence. Abstrak Keloid merupakan kelainan fibroproliferatif pada dermis akibat penyembuhan luka yang tidak normal, ditandai dengan deposisi kolagen yang berlebihan, penebalan dan vaskularisasi dermis yang tinggi, serta infiltrasi sel inflamasi yang melimpah. Insidensi keloid tertinggi terjadi pada individu pada usia dekade kedua. Ilustrasi Kasus: Seorang perempuan berusia 16 tahun datang ke Poliklinik Dermatologi dan Venereologi RS Prof. Chairuddin P. Lubis Medan dengan keluhan utama adanya benjolan di bagian depan dan belakang daun telinga kiri disertai rasa gatal sejak tiga tahun yang lalu. Awalnya, 4 tahun lalu, pasien mengeluh gatal setelah tindik telinga. Seiring waktu, benjolan muncul di lokasi penindikan. Benjolan tersebut dilaporkan bertambah besar secara bertahap selama 2 tahun terakhir. Pada pemeriksaan dermatologi terdapat bintil eritema soliter berbatas tegas, konsistensi padat seperti spons, bentuk bulat lonjong dan ukuran 1,4x1,3x0,9 cm, tepi teratur, permukaan licin pada daerah lobulus aurikularis anterior sinistra dan lobulus aurikularis posterior sinistra. Pasien didiagnosis dengan keloid. Pasien kemudian direncanakan untuk dilakukan eksisi bedah dengan teknik debulking dan injeksi triamcinolone acetonide intralesi. Pembahasan: Penatalaksanaan kombinasi merupakan strategi yang optimal dan sebagian besar penelitian ditemukan bahwa eksisi bedah yang dikombinasikan dengan injeksi steroid menunjukkan angka kekambuhan >50%. Kesimpulan: Pengobatan keloid sebaiknya dilakukan secara kombinasi untuk mengurangi kekambuhan.